Protective effects of sodium butyrate on fluorosis in rats by regulating bone homeostasis and serum metabolism - Ying Li; Fengmei Yang; Jie Liu; Mengqi Jiang; Ye Yu; Qingyi Zhou; Lu Sun; Zhuo Zhang; Lin Zhou (Ecotoxicology and Environmental Safety, 2024)
Fluorosis due to high fluoride levels in drinking water profoundly affects the development of human skeletal and dental structures. Sodium butyrate (NaB) has been found to regulate overall bone mass and prevent pathological bone loss. However, the mechanism of NaB action on fluorosis remains unclear. In this study, a rat model of fluorosis induced by 100 mg/L sodium fluoride was used to investigate the impact of NaB on bone homeostasis and serum metabolomics. It was found that NaB significantly reduced the levels of bone resorption markers CTX-Ⅰ and TRACP-5B in fluorosis rats. Moreover, NaB increased calcium and magnesium levels in bone, while decreasing phosphorus levels. In addition, NaB improved various bone microstructure parameters, including bone mineral density (BMD), trabecular thickness (Tb. Th), trabecular bone separation (Tb. SP), and structural model index (SMI) in the femur. Notably, NaB intervention also enhanced the antioxidant capacity of plasma in fluorosis rats. Furthermore, a comprehensive analysis of serum metabolomics by LC-MS revealed a significant reversal trend of seven biomarkers after the intervention of NaB. Finally, pathway enrichment analysis based on differential metabolites indicated that NaB exerted protective effects on fluorosis by modulating arginine and proline metabolic pathways. These findings suggest that NaB has a beneficial effect on fluorosis and can regulate bone homeostasis by ameliorating metabolic disorders.